Fear of love and its Relationship to the Emotional Intelligence of University Students - Al-Barwar, Rasheed Hussain Ahmed; Bakr , Mohamed Taha Hussein (Zanco Journal of Human Sciences, 2021)
The study aimed to identify the level of fear of love and emotional intelligence among university students, and to reveal the significance of the differences in fear of love and emotional intelligence according to the variables of gender, major of study, and study grade. As well as, the relationship between the two variables of fear of love and emotional intelligence. The study sample included (144) male and female students who were randomly chosen from fore scientific departments at the College of Basic Education at the University of Duhok.The study relied on two scales which are; the scale of Fear of Love, and the scale of Emotional Intelligence in collecting information after verifying their validity and reliability. The data were processed using the t-test for one sample, t-test for two independent samples, and ANOVA to analyze the date. The results showed that the level of fear of love among the individuals of the sample was high, and it was found that the level of emotional intelligence is low for them, and the results revealed that there are no significant differences in the level of fear of love as well that of emotional intelligence according to the variables of gender, major of study, and study grade. The results indicated a negative relationship between the two variables of fear of love and emotional intelligence. In light of the results, a set of recommendations and proposals were presented.